Measurements and performance characteristics of diagnostic x-ray tubes and generators - Shaw, Daniel (Researcher in clinical and radiation physics); Fazakerley, Jason; Honey, Ian; Saunders, Debbie (Radiation protection expert) (IOP (Series). Release 22., 2022)
This book describes the theoretical principals including potential modes of failures and equipment performance limitations and provides practical advice for making quality assurance (QA) measurements for clinical X-ray tubes and generators.